Proposing demand meet capacity waiting area for passenger at station Star LRT Masjid Jamek Kuala Lumpur - Muhammad Akmal , Yaakob (2013)
Level of Service (LOS) is a quality of measurement control that characterizes an operational condition. It's commonly used in measure traffic condition roadside to determine the level of effectiveness. However, a LOS measure for waiting area is not well developed until now. The primary objective of this study is to determine the levelof-service of the pedestrian walkway at Station STAR LRT Masjid Jamek Kuala Lumpur, in order to understand its current operational conditions. This research may adapt from the methodology of and Transit Capacity and Quality of Service Manual (TCQSM) to compute LOS of passenger. The results showed that the waiting area service in AmpanglSri Petaling line at LOS F on weekdays and LOS D on weekend. Thus, the operational condition of the walkway is poor condition and a waiting area cannot meet a demand capacity for passenger. Therefore, new design walkway width need to define to meet the purpose on desired level of service.